Afternoon tea: a timeless tradition (HTP283- Cafe Service Operation) / Noraini Rahim ... [et al.] - Rahim, Noraini; Hamir, Norhamizan; Mohd Akhir, Irina; Ismail, Anida (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Cafe Service Operation (HTP283) practical training class is a hands-on course that teaches students the skills they need to work in a cafe. Students will learn about food and beverage preparation, service, customer service, cash handling, and safety and sanitation. Students will be able to apply the technical and interpersonal skills required by daily’s waiters in cafe operation through different service set-ups and menus. The practical class will be held at the Mock Restaurant at the Faculty of Hotel and Tourism Management, Ground Floor, Hotel UiTM Pulau Pinang. This is where students will have the opportunity to apply the skills they have learned in the classroom. This practical class is a great opportunity for students who are interested in a career in the hospitality industry. One of the topics that we discussed in class is afternoon tea. The class includes 1 hour of theory and 5 hours of practical training where students learn how to prepare and serve afternoon tea. The class is taught by lecturers who are passionate about afternoon tea. Our practical afternoon tea class is a great way to learn the ins and outs of this classic British tradition. For two weeks, we covered different aspects of afternoon tea. From the history of the tradition to the different types of tea and sandwiches that are typically served. We also spend time practicing our mise en place and service skills. The class is very popular and seats are often sold out quickly.